2016
DOI: 10.1016/j.biocon.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of woodland birds as taxonomic surrogates in conservation planning for biodiversity on farms

Abstract: Woodland birds are a commonly used taxonomic surrogate for other species groups in agricultural landscapes as they are relatively diverse, easily-studied, and charismatic. Yet, other taxa can respond to native vegetation on farms differently to woodland birds, challenging the present focus on birds in agri-environmental schemes. We aimed to assess the effectiveness of woodland birds as taxonomic surrogates for biodiversity in conservation planning on farms, in comparison with reptiles and arboreal marsupials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Other avenues for research include: (i) exploring whether a taxon-specific focus on a small suite of threatened woodland birds leads to conservation outcomes for other woodland taxa, for example reptiles, arboreal marsupials and invertebrates that are known to respond differently to woodland patch types compared with birds (Cunningham et al 2007;Jellinek et al 2013;Jellinek et al 2014;Michael et al 2014;Ikin et al 2016b), (ii) exploring the applicability of our findings to other woodland and non-woodland agricultural systems, where patch types may be surrogates for different landscape features, and (iii) exploring how ecological function can be incorporated into conservation planning to improve conservation outcomes in agricultural landscapes (Klein et al 2009;Chan et al 2011).…”
Section: Priorities For Future Researchmentioning
confidence: 99%
“…Other avenues for research include: (i) exploring whether a taxon-specific focus on a small suite of threatened woodland birds leads to conservation outcomes for other woodland taxa, for example reptiles, arboreal marsupials and invertebrates that are known to respond differently to woodland patch types compared with birds (Cunningham et al 2007;Jellinek et al 2013;Jellinek et al 2014;Michael et al 2014;Ikin et al 2016b), (ii) exploring the applicability of our findings to other woodland and non-woodland agricultural systems, where patch types may be surrogates for different landscape features, and (iii) exploring how ecological function can be incorporated into conservation planning to improve conservation outcomes in agricultural landscapes (Klein et al 2009;Chan et al 2011).…”
Section: Priorities For Future Researchmentioning
confidence: 99%
“…Finally, we asked: (3) How similar are these best sets of habitat patches selected for each taxa, and at each defined representation target. We therefore compared the sets of woodland patches selected for each taxon at each representation target by assessing the degree of overlap (as measured with dissimilarity, distance metrics) in patch set solutions between taxa following Ikin et al (2016). Since many species in human-modified landscapes can be expected to be wideranging generalists rather than habitat specialists given the effects of biotic homogenisation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Still, they also described an anti‐surrogate, a selected focal species negatively associated with occurrence of other species. Another recent study found woodland birds were associated with targets for a subset of threatened birds, but not for reptiles or arboreal marsupials; finding that birds were a better surrogate for biodiversity than the other two taxa in this system (Ikin ). Nicholson et al.…”
Section: Introductionmentioning
confidence: 96%
“…Still, they also described an anti-surrogate, a selected focal species negatively associated with occurrence of other species. Another recent study found woodland birds were associated with targets for a subset of threatened birds, but not for reptiles or arboreal marsupials; finding that birds were a better surrogate for biodiversity than the other two taxa in this system (Ikin 2016). Nicholson et al (2013) demonstrated that focal species have merit as a conservation planning tool where vertebrate focal species were used as a proxy in decision making to select native forest reserves in Australia.…”
Section: Introductionmentioning
confidence: 99%